Cross-country artificial intelligence policy mapping: Human-centered governance and industrial adoption prospects in Indonesia - Dedy Permadi (JURNAL ILMU SOSIAL, 2026)
This study analyzes Artificial Intelligence (AI) governance through a comparative study of regulatory frameworks in the United States (innovation-based), the European Union (risk-based), Spain (regulatory sandbox experimentation), and China (state-led sectoral). These four jurisdictions were selected to illustrate the operationalization of Human-Centered Artificial Intelligence (HCAI) principles, namely reliability, safety, and trust, through different governance pathways. Current literature on AI governance predominantly focuses on the discussion of the great power rivalry, while the gap between global standards and domestic readiness of middle-power nations like Indonesia remains underexamined. As a Global South country with complex development contexts, Indonesia cannot adopt a single governance model. This study argues that Indonesia’s AI governance must transition from a risk-mitigation focus toward a hybrid approach based on readiness, incentives, and participation. A hybrid approach is more effective in integrating ethical guidelines, proportional regulation, policy experimentation, and sectoral rules in a phased manner. Integrating HCAI principles into Indonesia’s digital transformation will enable equitable AI diffusion, strengthen human oversight, and align national agenda with global norm standards. This study emphasizes the urgency of strategic policies to ensure AI adoption in Indonesia fulfills socio-economic development needs, rather than serving as mere performative policy.